TDMA scheduling design of multihop packet radio networks based on latin squares. - Ji-Her Ju (IEEE Journal on selected areas in communications)
Many transmission scheduling algorithms have been proposed to maximize spatial reuse and minimize the time division multiple access (TDMA) frame length in multihop packet radio networks. Almost all existing algorithms assume exact network topology information and require recomputations when the network topology changes. In addition, existing work focuses on single channel TDMA systems. In this paper, we propose a multichannel topology-transparent algorithm based on latin squares. The proposed algorithm has the flexibility to allow the growth of the network, i.e., the network can add more mobile nodes without recomputation of transmission schedules for existing nodes. At the same time, a minimum throughput is guaranteed. We analyze the efficiency of this algorithm and examine the topology-transparent characteristics and the sensitivity on design parameters by analytical and simulation techniques